Colombia's Policy Pathways - International Water Management Institute (International Water Management Institute, 2024)
Join us in Colombia for Episode 4 of Policy Pathways! We are delighted to welcome back Augusto Castro Nuñez, Lead author for Colombia's NPS Policy Coherence report and Senior Scientist at Alliance-CIAT. Castro Nuñez is joined by Miguel Peña Varón, Senior Researcher at the CINARA Institute of Universidad del Valle. Our fantastic guests offer their expertise and insight on Colombia's sustainable development policy.